Prewedding Practices as Premarital Behavior in Muslim Society: An Analysis of Tafsir Al-Misbah on Qur’an 17:32 - Minta Ito Dongoran; Uqbatul Khoir Rambe (Journal of Indonesian Islamic Studies, 2026)
This study examines prewedding practices as a form of premarital behavior in Tarapung Raya Village, South Tapanuli Regency, and analyzes their ethical implications through the perspective of Tafsir Al-Misbah on QS. Al-Isra’ verse 32. This study addresses an important gap in existing scholarship, as previous studies have largely discussed prewedding practices from general Islamic legal perspectives, while limited attention has been given to empirical analysis grounded in Qur’anic ethics, particularly in rural Muslim communities. This research employs a qualitative method with a descriptive approach. Data were collected through observation, semi-structured interviews, and documentation involving couples who conducted prewedding photography, religious leaders, and community figures. The findings reveal that prewedding photography has become increasingly normalized as part of contemporary wedding culture, influenced by modernization, digital visual culture, and changing social trends. The practice is no longer viewed merely as wedding documentation but also as a medium for romantic expression, emotional intimacy, and social prestige. The findings further indicate that prewedding sessions commonly involve physical interactions such as holding hands, hugging, close body positioning, and forehead kissing between unmarried couples. From the perspective of Tafsir Al-Misbah on QS. Al-Isra’ verse 32, such interactions may be categorized as behaviors approaching zina (muqaddimat al-zina) because they potentially cross Islamic ethical boundaries concerning modesty, physical interaction, and moral restraint. The study demonstrates that the ethical evaluation of prewedding practices cannot be based solely on social normalization or cultural acceptance. Instead, such practices must be assessed through Islamic preventive ethics that emphasize dignity, self-control, and the avoidance of behaviors potentially leading to moral transgression. This study contributes to contemporary Islamic studies by highlighting the tension between modern visual culture and Islamic morality, while offering a Qur’anic ethical framework for critically evaluating emerging social practices in Muslim communities.